Forms of talk - Goffman, Erving (Oxford Blackwell, 1981)
Forms of Talk extends Erving Goffman's interactional analyses of face-to-face communication to ordinary conversations and vebal exchanges. In this, his most sociolinguistic work, Goffman relates to certain forms of talk some of the issues that concerned him in his work on frame analysis. This book brings together five of Goffman's essays: "Replies and Responses," "Response Cries," "Footing," "The Lecture," and "Radio Talk."
Includes index.
Keywords: Oral communication